Antimicrobial peptides - Phoenix, David, 1966-; Dennison, Sarah R.; Harris, Frederick (Wiley-VCH, 2013)
"In this didactically-written text, the small team of expert authors presents the field in a comprehensive and accessible manner that is well suited for students and junior researchers. The result is a highly readable and systematically structured introduction to antimicrobial peptides, their structure, biological function and mode of action. The authors point the way towards a rational design of this potentially highly effective new class of clinical antibiotics on the brink of industrial application by discussing their design principles, target membranes and structure-activity relationship."--Resumé vydavatele
Keywords: peptidy; antimikrobiální látky; antibiotika; peptidy -- terapeutické aspekty; peptids; anti-microbial agents; antibiotics; peptids -- therapeutic aspects; elektronické knihy; electronic books